2021
DOI: 10.1038/s41467-021-22920-8
|View full text |Cite
|
Sign up to set email alerts
|

Subtelomeric assembly of a multi-gene pathway for antimicrobial defense compounds in cereals

Abstract: Non-random gene organization in eukaryotes plays a significant role in genome evolution. Here, we investigate the origin of a biosynthetic gene cluster for production of defence compounds in oat—the avenacin cluster. We elucidate the structure and organisation of this 12-gene cluster, characterise the last two missing pathway steps, and reconstitute the entire pathway in tobacco by transient expression. We show that the cluster has formed de novo since the divergence of oats in a subtelomeric region of the gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
80
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 62 publications
(86 citation statements)
references
References 98 publications
(119 reference statements)
3
80
0
Order By: Relevance
“…In addition, genome analysis of poppy revealed that noscapine and thebaine clusters occur separately on the same chromosome while R -reticuline-synthesizing genes were found to be loosely clustered (Guo et al, 2018 ; Li et al, 2020 ). A similar pattern of compact clustering is also observed in oat avenacin cluster (Qi et al, 2004 ; Li et al, 2021a ). Recently, elucidation of complete cluster organization of avenacins revealed that all genes are organized in a co-linear manner in relation to the biosynthetic steps of the pathway, and ten genes are arranged on the end of long arm of the chromosome 1 while the other two glycosyl transferases (GTs) are present in proximal scaffold (Li et al, 2021a ).…”
Section: Organization Of Plant Gene Clusterssupporting
confidence: 72%
See 2 more Smart Citations
“…In addition, genome analysis of poppy revealed that noscapine and thebaine clusters occur separately on the same chromosome while R -reticuline-synthesizing genes were found to be loosely clustered (Guo et al, 2018 ; Li et al, 2020 ). A similar pattern of compact clustering is also observed in oat avenacin cluster (Qi et al, 2004 ; Li et al, 2021a ). Recently, elucidation of complete cluster organization of avenacins revealed that all genes are organized in a co-linear manner in relation to the biosynthetic steps of the pathway, and ten genes are arranged on the end of long arm of the chromosome 1 while the other two glycosyl transferases (GTs) are present in proximal scaffold (Li et al, 2021a ).…”
Section: Organization Of Plant Gene Clusterssupporting
confidence: 72%
“…Genome analysis of A. strigosa revealed the presence of avenacin cluster in sub-telomeric regions, with the presence of the early pathway genes near to the telomere, and the existence of terminal pathway genes away from the telomere. These typical positioning co-linearity of genes in the cluster is considered to avoid the deletions of terminal pathway genes, thus preventing the accumulation of toxic intermediates (Li et al, 2021a ). On the other hand, maize DIMBOA gene cluster is also located at the tip (telomeric region) of the chromosome for facilitating an adaptive evolution and a coordinated regulation (Dutartre et al, 2012 ).…”
Section: Evolutionary Dynamics Of Plant Gene Clustersmentioning
confidence: 99%
See 1 more Smart Citation
“…Clustering has thus facilitated delineation of various plant biosynthetic pathways, including complex pathways for alkaloids [31,47] and terpenes [48]. Additionally, once a BGC is discovered in one plant species, similar clusters can in some cases be identified in related species by searching for clustered orthologs or syntenic regions [27,30].…”
Section: Clustering Facilitates Pathway Discovery and Elucidationmentioning
confidence: 99%
“…In instances where biosynthetic pathway genes are clustered and genome sequences are available, discovery of one gene in a pathway can lead to identification of others, simply by searching for flanking genes with relevant functional annotations. Clustering has thus facilitated delineation of various plant biosynthetic pathways, including complex pathways for alkaloids [ 31 , 47 ] and terpenes [ 48 ]. Additionally, once a BGC is discovered in one plant species, similar clusters can in some cases be identified in related species by searching for clustered orthologs or syntenic regions [ 27 , 30 ].…”
Section: Clustering Facilitates Pathway Discovery and Elucidationmentioning
confidence: 99%